REPRESENTASI GAYA HIDUP SEHAT DALAM WEB SERIES “SORE” - Chelsea Maulia; Nadya Ishma Ashila; Siggi Amalia Bertianto (SOSIOEDUKASI, 2021)
This research was conducted based on the phenomenon of delivering messages through the representation of a healthy lifestyle through the "afternoon" web series implicitly and wrapped so attractively, so that the advertisements made through the web series are not only persuasive but also have a unique, entertaining storyline. The purpose of this study is to show the meaning of a sign or symbol that represents a healthy lifestyle using Roland Barthes's semiotic analysis approach in the "afternoon" web series. The research method used in the research in this study is qualitative, intended to gather information about the reality of people's consumption culture about how to represent healthy lifestyles in the "afternoon" web series. Data collection is done by downloading and watching the "afternoon" web series that represents a healthy lifestyle using Roland Barthes's semiotic analysis which has connotation and denotation elements then presented in one table. The results of this study explain the representation of a healthy lifestyle in the form of maintaining eating patterns, regulating sleep patterns, exercising regularly and avoiding things that can adversely affect the health of the body. The meaning of a sign or symbol of a healthy lifestyle contained therein is about the importance of maintaining a healthy body not only for yourself but for the environment by changing lifestyle to be healthier.